Pengaruh Pertumbuhan Ekonomi, Upah Minimum Regional dan Indeks Pembangunan Manusia terhadap Kemiskinan Kabupaten/Kota di Provinsi Riau - Tampubolon, Dahlan; Mainingsih, Fitria Rahayu (SAFE-Network, 2024)
The aim of this research is to analyze the influence of economic growth, minimum wages and the Human Development Index on poverty in districts/cities in Riau Province. This research is quantitative descriptive research using panel data, the data used is in the form of time series (2010-2022) and cross sections (12 regencies/cities in Riau Province). The type of data used in this research is secondary data obtained from the Central Statistics Agency (BPS) and supporting journals. The analytical method used is the Delangan Panel Linear Data Regression Analysis Method. The Fem method uses the Eview software tool 6. The results of the research show that the positive and negative influence on the poverty of districts/cities in Riau Province is used.